The Impact of Forest Fires on Ecosystem Services: The Case of Greece - Misseyanni, Anastasia; Christopoulou, Anastasia; Kougkoulos, Ioannis; Vassilakis, Emmanuel; Arianoutsou, Margarita (Forests, 2025)
(1) Background: The present study examines the effects of fire on the ecosystem services of forest ecosystems in Greece. Being a Mediterranean country, Greece has been affected by fires of increasing intensity and frequency in recent years; (2) Methods: Information was extracted from 56 articles published in the period January 1997–March 2024 that were selected after an extensive literature review; (3) Results: An increasing trend in the number of published articles over time was observed. Studies on regulating and maintenance services prevailed. The majority of studies reported on thermo-Mediterranean ecosystems, with Pinus halepensis Mill forests being the most common ecosystems affected by fires. The effects of fire were primarily negative on provisioning and cultural services, as well as on the control of erosion rates, regulation of the hydrologic cycle, atmospheric composition, and climate regulation. Most effects on plant diversity were found to be positive, while positive and neutral effects were also recorded for pollination. The most pronounced negative or positive effects were noted for the first two years after the fire. The spatial mapping of the results showed that the areas most affected by the fires in Greece are Eastern Attica, Euboea, Western Attica, and most regional units of the Peloponnese; (4) Conclusions: In the era of climate change and changing fire regimes in the Mediterranean, there is a need to further research the impact of fire on ecosystem services, as this will help in the better protection and management of the most vulnerable forest ecosystems.